2004
DOI: 10.1079/phn2003525
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a computer-based nutrition education tool

Abstract: Objective: To evaluate the efficacy and feasibility of using a computer-based teaching tool (http://www.coolfoodplanet.org) for nutrition and lifestyle education developed for primary school children. Design: This was a 2-week school-based intervention in third and fourth grades. The study design was multi-factorial with repeated measures of nutrition knowledge, at three points in time, of dependent samples from control and intervention groups. Control schools (n ¼ 7) used 'traditional' nutrition education mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 13 publications
(9 reference statements)
0
32
0
Order By: Relevance
“…In another study, almost all of the pupils (97 %) indicated that they wanted to join in the intervention again, while only two pupils (1?2 %) gave the grade 'not good at all' to the intervention (50) .…”
Section: Degree Of Satisfaction With Interventionmentioning
confidence: 96%
See 3 more Smart Citations
“…In another study, almost all of the pupils (97 %) indicated that they wanted to join in the intervention again, while only two pupils (1?2 %) gave the grade 'not good at all' to the intervention (50) .…”
Section: Degree Of Satisfaction With Interventionmentioning
confidence: 96%
“…Pupils in the intervention school demonstrated healthier snack selection at school and a greater uptake of school meals There was no significant change in the participants' conceptual understanding of food Kreisel (50) To evaluate the efficacy and feasibility of using a computer-based teaching tool for nutrition and lifestyle education developed for primaryschool children…”
Section: Studies Included In Qualitative Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Schools provide the most effective and efficient way to reach a large segment of the population, including young people, their families and the community in general 8 . Hence, the development of innovative nutrition education curricula is a continuous and demanding process 9 . Keeping this in mind, the Food and Agriculture Organization of the United Nations (FAO) along with a group of international and non-governmental organisations has launched a global education initiative called 'Feeding Minds, Fighting Hunger' (FMFH) with the aim of educating and motivating schoolchildren to get actively involved in creating a world free from hunger and malnutrition.…”
mentioning
confidence: 99%